Illicium parviflorum Anise, Yellow Anisetree, Star Anise - Edward Gilman (EDIS)
This document provides an insightful overview of the longstalk holly, a broadleaf evergreen native to East Asia. It highlights the plant’s ornamental qualities, such as its smooth leaves, pyramidal shape, and red fruits that attract birds. The text also discusses the longstalk holly’s growth preferences, including its partial shade requirement and tolerance to wind and cold. The document concludes with potential landscaping applications for the plant, emphasizing its suitability for hedges, screens, and container plantings. Original publication date October 1999.